PENEGAKAN HUKUM TERHADAP PELAKU PELECEHAN SEKSUAL DIBAWAH UMUR (Studi Kasus : Pelecehan Seksual di SMP X ) - Madeleine Lie; Elisa Novianti; Windisen Windisen; Gavinela Clarissa; Ratu Shyfa N.C. (Jurnal Hukum Adigama, 2021)
Sexual harassment in Indonesia is rife, especially in educational institutions. This sexual harassment itself can be done by anyone, whether teachers, staff or students in the school. Sadly, cases of sexual harassment that occur in educational institutions in Indonesia are rarely investigated by schools or the authorities on the grounds that "things like this should be dealt with in a family way.", To protect the reputation of the school or think that by punishing the perpetrator then the perpetrator's future will be destroyed. As happened in a Catholic school in Pademangan, SMP. X where G (name suppressed) sexually harassed several female students (believed to be J, Y, and A (name also changed)) who were in the same class as him using various means via Whatsapp and the school only scold his parents instead of expelling him which is a pattern in this school even thou in the school’s rule book says that if the student did immoral behavior such as sexual harassment, then the student will get expelled.Since what G did was a criminal act, then G should have received a legal penalty. It's just that because he is less than 12 years old according to the SPPA Law, he is only returned to his parents and fostered by the social agency.